Reorienting Investment Dispute Resolution in Indonesia: Towards a Fair and Efficient System - Sahat Poltak Siallagan; Jamal Wiwoho; Arief Suryono; Itok Dwi Kurniawan; Acacio Fernandes (Journal of Law and Legal Reform, 2024)
In the era of Industry 4.0, the surge in foreign investment and the proliferation of global trade agreements have intensified the need for more reliable dispute resolution mechanisms. While the Investor-State Dispute Settlement (ISDS) system has long been the standard, it faces widespread criticism for its lack of transparency, fairness, and absence of an appellate mechanism. In response, the Investment Court System (ICS) has emerged as a novel alternative, introducing significant reforms such as the appointment of more qualified arbitrators, greater neutrality, enhanced transparency, and, crucially, a structured appeals process that offers stronger legal certainty. Although no disputes have yet been resolved through ICS, raising questions about its efficiency, the system represents a promising advancement in creating a more equitable and trustworthy framework. The appellate mechanism of ICS, in particular, addresses a critical shortcoming of ISDS, where arbitration awards are often challenged in national courts, leading to legal uncertainty. By balancing investor protection with state sovereignty to regulate in the public interest, ICS has the potential to enhance legal clarity, foster public confidence, and create a more stable and inclusive global investment environment.